A Microwave Synthesis of Mesoporous NiCo2O4 Nanosheets as Electrode Materials for Lithium-Ion Batteries and Supercapacitors - Mondal, Anjon Kumar; Su, Dawei; Chen, Shuangqiang; Kretschmer, Katja; Xie, Xiuqiang; Ahn, Hyo-Jun; Wang, Guoxiu (Chemphyschem, 2015)
A facile microwave method was employed to synthesize NiCo2O4 nanosheets as electrode materials for lithium‐ion batteries and supercapacitors. The structure and morphology of the materials were characterized by X‐ray diffraction, field‐emission scanning electron microscopy, transmission electron microscopy and Brunauer–Emmett–Teller methods. Owing to the porous nanosheet structure, the NiCo2O4 electrodes exhibited a high reversible capacity of 891 mA h g−1 at a current density of 100 mA g−1, good rate capability and stable cycling performance. When used as electrode materials for supercapacitors, NiCo2O4 nanosheets demonstrated a specific capacitance of 400 F g−1 at a current density of 20 A g−1 and superior cycling stability over 5000 cycles. The excellent electrochemical performance could be ascribed to the thin porous structure of the nanosheets, which provides a high specific surface area to increase the electrode–electrolyte contact area and facilitate rapid ion transport. Pore‐table electronics: A facile microwave method was used to synthesize mesoporous NiCo2O4 nanosheets as electrode materials for Li‐ion batteries and supercapacitors. The NiCo2O4 electrodes exhibited a high reversible capacity of 891 mA h g−1 at a current density of 100 mA g−1, good rate capability and stable cycling performance. When used in supercapacitors, NiCo2O4 nanosheets showed superior pseudocapacitive performance and excellent cycling stability (4.8 % loss after 5000 cycles).